Effect of low‐dose supplements of menaquinone‐7 (vitamin K2) on the stability of oral anticoagulant treatment: dose–response relationship in healthy volunteers - Theuwissen, E.; Teunissen, K. J.; Spronk, H. M. H.; Hamulyák, K.; Ten Cate, H.; Shearer, M. J.; Vermeer, C.; Schurgers, L. J. (Journal of thrombosis and haemostasis, 2013)
Summary Background and Objective Despite the worldwide use of vitamin K antagonists (VKAs), there is limited knowledge of the influence of dietary vitamin K on anticoagulation control. In view of the increasing nutraceutical availability of menaquinone‐7 (MK‐7; vitamin K2) and its promotion for bone and cardiovascular health, it is important to determine the posology for the interference of supplemental MK‐7 with VKA therapy. Patients Eighteen healthy men and women were anticoagulated for 4 weeks with acenocoumarol, and 15 of them attained a target International Normalized Ratio (INR) of 2.0. In the six subsequent weeks, subjects were given increasing doses of MK‐7 (10, 20 and 45 μg day−1) while continuing acenocoumarol treatment at established individual doses. Results Apart from the INR, acenocoumarol treatment significantly increased the levels of uncarboxylated factor II (ucFII), uncarboxylated osteocalcin (ucOC), and desphospho‐uncarboxylated matrix Gla‐protein (dp‐ucMGP), and decreased endogenous thrombin generation (ETP). A daily intake of 45 μg of MK‐7 significantly decreased the group mean values of both the INR and ucFII by ~ 40%. Daily intakes of 10 and 20 μg of MK‐7 were independently judged by two hematologists to cause a clinically relevant lowering of the INR in at least 40% and 60% of subjects, respectively, and to significantly increase ETP by ~ 20% and ~ 30%, respectively. Circulating ucOC and dp‐ucMGP were not affected by MK‐7 intake. Conclusions MK‐7 supplementation at doses as low as 10 μg (lower than the usual retail dose of 45 μg) significantly influenced anticoagulation sensitivity in some individuals. Hence, the use of MK‐7 supplements needs to be avoided in patients receiving VKA therapy.